Ask Question
11 May, 03:29

Solve this equation with substitution method : -

x+5 = 3 (y+5)

x-5 = 7 (y-5)

+2
Answers (1)
  1. 11 May, 07:21
    0
    From the first equation,

    x+5 = 3 (y+5)

    x = 3y + 15 - 5

    Now substitue x in the second equation with (3y + 15 - 5).

    x-5 = 7 (y-5)

    (3y+15-5) - 5 = 7 (y-5)

    3y + 5 = 7y - 35

    -4y = - 40

    y = 10

    Since y is 10, and x is (3y + 15 - 5),

    x = 30 + 15 - 5 = 40
Know the Answer?
Not Sure About the Answer?
Find an answer to your question ✅ “Solve this equation with substitution method : - x+5 = 3 (y+5) x-5 = 7 (y-5) ...” in 📘 Mathematics if you're in doubt about the correctness of the answers or there's no answer, then try to use the smart search and find answers to the similar questions.
Search for Other Answers